Cervical poorly differentiated adenocarcinoma with dominant choriocarcinomatous pattern: A case report - Nikolić Branka; Ćurković Aleksandar; Dragojević-Dikić Svetlana; Mitrović Ana; Kuzmanović Igor; Aranđelović Aleksandra; Stanković Goran (Vojnosanitetski Pregled)
Introduction. Gestational trophoblastic neoplasm (GTN), choriocarcinoma in coexistence with primary cervical adenocarcinoma, is a rare event not easy to diagnose. Choriocarcinoma is a malignant form of GTN but curable if metastases do not appear early and spread fast. Case report. We presented choriocarcinoma in coexistence with primary cervical adenocarcinoma in a 48-year-old patient who had radical hysterectomy because of confirmed cervical carcinoma (Dg: Carcinoma porto vaginalis uteri FIGO st I B1). Histological findings confirmed cervical choriocarcinoma with extensive vascular invasion and apoptosis but GTN choriocarcinoma was finally confirmed after immunohystochemical examinations. Preoperative serum human gonadotropine (beta hCG) level stayed unknown. This patient did not have any pregnancy-like symptoms before the operation. The first beta hCG monitoring was done two months after the operation and found negative. According to the final diagnosis the decision of Consilium for Malignant Diseases was that this patient needed serum hCG monitoring as well as treatment with chemotherapy for high-risk GTN and consequent irradiation for adenocarcinoma. Conclusion. The early and proper diagnosis of nonmetastatic choriocarcinoma of nongestational origine in coexistence with cervical carcinoma is curable and can have good prognosis.